Peningkatan Pengetahuan Masyarakat dalam Pencegahan Penyakit DBD di Desa Beti Indralaya Selatan Ogan Ilir - Ramayanti, Indri; Erlyn, Putri; Noviyanti, Noviyanti; Silvana, Rista; Prayogi, Fandika Dhimas (Indonesia Berdaya, 2022)
Dengue Hemorrhagic Fever (DHF) morbidity and mortality continue to occur in Indonesia year after year, so activities to eradicate mosquito nests must be carried out with the participation of all levels of society. One of the programs that can be implemented in health education is to provide understanding, knowledge, and public awareness. This activity aims to increase public awareness and attitudes toward dengue fever prevention. The lecture method, audio-visual media, teaching aids, and discussion are used in the implementation. Women members of the Family Welfare Programme in Beti Village, South Inderalaya District, Ogan Ilir Regency were given community service. There were as many as 38 people who responded. Activities are evaluated using a questionnaire distributed at the start and end of the activity. The activity's outcomes demonstrated an increase in knowledge about DHF prevention. Conclusion: Counseling the community about dengue fever has a positive impact on raising public awareness and knowledge about DHF prevention.